Application of GGE biplot analyses for characterizing diverse sesame (Sesamum indicum) germplasm for yield and yield-contributing traits - Kumar, Hitesh; Kaur, Gurpreet; Banga, Shashi (The Indian Journal of Agricultural Sciences, 2012)
A representative sample of 146 diverse sesame accessions, originating from 26 countries and assigned into six groups on the basis of their eco- geographical origin, was characterized for yield and yield-contributing traits using “GGE biplot analyses”. ‘Which-won-where’ application of GGE biplot was used to rank accessions of each group on the basis of collective trait contributions to individual accession. Eighteen promising accessions having combination of positive traits (PI 202722Myanmar, PI 223713India, PI 220664Afghanistan, PI 285173Israel, PI 165021Turkey, PI 170711Turkey, PI 490063South Korea, PI 490033South Korea, PI 345669Soviet Union, PI 561705Mexico, PI 594909Mexico, PI 280790United States, PI 198155Egypt, PI 189081Cameroon, PI 246386Zaire, Pragati India, SVPR 1India, ACHBB 97India) were identified. Correlation coefficient analysis (GGE biplot) as carried out over two years, revealed that total pods/plant (r=0.453**, 0.24**), pods on main shoot (r=0.337**, 0.492**) and seeds/pod (r=0.268**, 0.254**) were the main yield-contributing traits in sesame. Per cent oil content/protein content had no inverse relationship with yield which makes it possible to combine high yield and high oil content in sesame cultivars. A select group of accessions (24) were also compared for stability of performance over two years. Altogether changed ranking was observed for majority of the accessions during second year indicating their differential genonotype × environment response; however one accession PI 223713 was identified which was stable for high yield and yield contributing traits across two years.